Strategi Green Marketing The Body Shop dalam Meningkatkan Brand Awareness Melalui Key Opinion Leader (KOL) di Instagram - Bella Pratiwi Rachman; Suci Indah Sya’baniah; Salsabila Sucita; Zwita Nur Azizah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The research intends to analyze how The Body Shop implements green marketing strategies through Key Opinion Leaders (KOLs) on Instagram to strengthen brand awareness in the competitive cosmetic industry. The research focused on examining the integration of green awareness, eco-label, and eco-brand elements with the VisCAP model as the foundation of KOL selection. This study used a descriptive qualitative approach. Data were collected through in-depth interviews, observation of Instagram content, and documentation from the official accounts @thebodyshopindo and @thebodyshopindo.impact. Purposive sampling was applied to select six informants, consisting of The Body Shop consumers and followers of relevant KOLs. Data analysis followed the Miles and Huberman interactive model involving reduction, presentation, and conclusion drawing, with validity ensured through triangulation of techniques and sources. The findings reveal that The Body Shop’s green marketing strategy is effectively communicated through Instagram-based KOL collaborations that consistently emphasize sustainability. KOL content integrates elements of green awareness, eco-label, and eco-brand through visual cues, educational narratives, and transparency regarding natural ingredients and cruelty-free practices. The VisCAP model (Visibility, Credibility, Attraction, Power) strongly guides the selection of KOLs such as @sustainable_suzy, whose environmental expertise enhances message authenticity. This collaboration significantly increases brand awareness across four indicators: recall, recognition, purchase intention, and consumption demonstrated through consumer engagement, increased interest in refill programs, and positive responses to sustainability campaigns. The study concludes that green marketing through KOL collaboration on Instagram effectively enhances The Body Shop’s brand awareness by harmonizing sustainability messages with credible influencer communication. Future research should compare micro- and macro-KOL effectiveness across different platforms such as TikTok to explore variations in strategic outcomes.